2001
DOI: 10.2527/2001.794934x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharmacological concentrations of zinc oxide with or without the inclusion of an antibacterial agent on nursery pig performance.

Abstract: A study involving nine research stations from the NCR-42 Swine Nutrition Committee used a total of 1,978 crossbred pigs to evaluate the effects of dietary ZnO concentrations with or without an antibacterial agent on postweaning pig performance. In Exp. 1, seven stations (IA, MI, MN, MO, NE, ND, and OH) evaluated the efficacy of ZnO when fed to nursery pigs at 0, 500, 1,000, 2,000, or 3,000 mg Zn/kg for a 28-d postweaning period. A randomized complete block experiment was conducted in 24 replicates using a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
108
1
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 15 publications
27
108
1
9
Order By: Relevance
“…Plasma Zn was affected by pharmacological Zn at both stages as piglets receiving ZnO at 3000 mg/kg had plasma Zn in the range of 1.5 to 1.9 mg/l, which is lower than values reported by Hill et al (2001) but perfectly aligned with those reported by Carlson et al (1999); piglets receiving microencapsulated ZnO, instead, did not differ from control and reported values comprised between 0.65 and 1.2 mg/l, which is in accordance with values for adequate Zn intake (Carlson et al, 1999). However, according to Hahn and Baker (1993), only Zn treatments that resulted in Zn plasma values of ∼1.5 mg/l were associated with improved gains that tended to be higher than those associated with Zn plasma values lower than 1.5 mg/l or higher than 3.0 mg/l.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Plasma Zn was affected by pharmacological Zn at both stages as piglets receiving ZnO at 3000 mg/kg had plasma Zn in the range of 1.5 to 1.9 mg/l, which is lower than values reported by Hill et al (2001) but perfectly aligned with those reported by Carlson et al (1999); piglets receiving microencapsulated ZnO, instead, did not differ from control and reported values comprised between 0.65 and 1.2 mg/l, which is in accordance with values for adequate Zn intake (Carlson et al, 1999). However, according to Hahn and Baker (1993), only Zn treatments that resulted in Zn plasma values of ∼1.5 mg/l were associated with improved gains that tended to be higher than those associated with Zn plasma values lower than 1.5 mg/l or higher than 3.0 mg/l.…”
Section: Discussioncontrasting
confidence: 64%
“…Dietary inclusion of ZnO at 2000 to 3000 mg/kg is extensively used in worldwide pig production, and past research has consistently proved the beneficial effects during the postweaning phase (Hill et al, 2001). However, increasing concerns on environmental pollution drove European legislators toward a more attentive policy on the excretion of heavy metals in manure (European Commission, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A base de dados foi desenvolvida a partir de 18 artigos (Hahn & Baker, 1993;Wedekind et al, 1994;Adeola et al, 1995;Poulsen & Larsen, 1995;Luo & Dove, 1996;Schell & Kornegay, 1996;Swinkels et al, 1996;Cheng et al, 1998;Carlson et al, 1999;Hill et al, 2000;Schiavon et al, 2000;Hill et al, 2001;Case & Carlson, 2002;Revy et al, 2002 As variáveis dependentes foram as concentrações plasmáticas de Zn e Cu e o ganho de peso e as variáveis nutricionais consideradas na análise, a ingestão de PB, lisina, Ca, P total, Cu e Zn. Os nutrientes ingeridos foram calculados com base na matéria natural por intermédio de dados de consumo dos animais e composição nutricional da dieta.…”
Section: Methodsunclassified
“…Devido a sua biodisponibilidade, o óxido de zinco é incluído nas dietas de leitões em fase de creche em concentrações aproximadas de 3000mg Zn/kg de ração como um promotor de crescimento e como preventivo na ocorrência de diarréia pós-desmame (HILL et al, 2001). …”
Section: Zinco Na Dieta De Leitõesunclassified